Diferentes concentrações espermáticas na inseminação artificial intra-uterina em suínos - Miller, Joana (2007)
The aim of this work was to evaluate the efficiency of the intrauterine insemination (IUI) in swine, considering the conception rate, farrowing rate, litter size (alive, stillborn and mummified) and pig born weight. In the IUI, the females had been inseminated at 24 and 48 hours after the oestrus detection, and had been used the inseminating doses with 500 million, 1 billion, 1.5 billion and 2 billion spermatozoa in 20 mL of extender. The procedure of catheter insertion through the cervical canal was successfully performed in 97,9% of females. It was carried out the conception rate from the 18th day and ultrasonic pregnancy diagnosis was undertaken at 28-30 days post-service. The conception rate was of 6,3% in the IUI. The farrowing rate in IUI was of 87,2%, being the farrowing rate in 100% for the spermatic concentration of 500 million. In relation with the number of born pigs, alive, stillborn, mummified and pig born weight observed in the females inseminated with IUI did not differ (P>0.05). The use of the concentration of 500 x 106 spermatozoa in 20 mL of extender, with intrauterine insemination, result in optimal reproductive performance.